Importance of Oral and Dental Health in the Elderly - Chrudimská, Lucie; Koutná, Kateřina (University of Pardubice, 2017)
Introduction: Oral health has a significant impact on the overall health condition. Both the lay public and experts often underestimate this problem area. Apart from the health of the oral cavity itself and overall health, care for one’s oral health improves overall quality of life. The condition of oral health in the elderly population is not at the desired level. To a great extent, oral health can be influenced by correct care. More attention should be paid to educating the population and the subjective area of self-care should not be underestimated. Objective: The objective of the study was to point out the importance of oral health in the context of overall health and to present the condition of seniors’ oral health as well as their interest in care for the oral cavity (including dentures). Method: A research probe was used, with a combination of quantitative and qualitative techniques in the process of data collection and analysis. We used our own questionnaire and semi-structured interviewing. The total number of respondents was 36 in the quantitative part and 7 in the qualitative part. Respondents in both parts of the study were elderly persons – members of a selected senior club older than 65 years. Respondents’ cognitive status was determined by means of the clock drawing test. The questionnaire data were processed using statistical software STATISTICA©. Results: The oral health condition in the selected sample of seniors is lower than desirable. Seniors in the research sample have no complex knowledge in the area of dental and oral care although they are interested in it. They are not aware of the impact of oral health on the overall health condition. Conclusion: The research probe implies that public awareness of this subject matter should be continuously and systematically increased. Multidisciplinary importance of oral health must be emphasized. An educational lesson was provided in the senior club and educational posters and leaflets were created in reaction to the results of the research probe.
Keywords: education; elderly people; knowledge; oral health; overall health